Analisis Determinan Harga Beras di Kabupaten Padang Pariaman - Indah Lestari; Joan Marta; Doni Satria (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
This study aims to analyze; (1) the impact of the amount of rice production on the rice price in Padang Pariaman (2) the effect of dry threshed paddy (Gabah Kering Panen/GKP)  price on the rice price in Padang Pariaman (3) the effect of unhusked dry rice ready for milling (Gabah Kering Giling/GKP) price on the rice price in Padang Pariaman (4) the influence of the Pekanbaru rice price on the Padang Pariaman rice price. The data used is monthly  from 2018-2020. Analysis used analysis Ordinary Least Square (OLS). The results showed that (1) the amount of rice production had a negative and significant effect on the price of rice in Padang Pariaman (2) the price of GKP had a positive and significant impact  on the price of rice in Padang Pariaman (3) the price of GKG had a positive and significant effect on rice prices. significant effect on rice prices in Padang Pariaman (4) Pekanbaru rice prices have a positive and significant impact on Padang Pariaman rice prices